Comparing Traumatic Brain Injury Symptoms Reported via Questionnaires Versus a Novel Structured Interview. (23rd February 2022) - Emmert, Natalie A.; Ristow, Georgia; McCrea, Michael A.; deRoon-Cassini, Terri A.; Nelson, Lindsay D.
Abstract: Objective: Mild traumatic brain injury (mTBI) symptoms are typically assessed via questionnaires in research, yet questionnaires may be more prone to biases than direct clinical interviews. We compared mTBI symptoms reported on two widely used self-report inventories and the novel Structured Interview of TBI Symptoms (SITS). Second, we explored the association between acquiescence response bias and symptom reporting across modes of assessment. Method: Level 1 trauma center patients with mTBI ( N = 73) were recruited within 2 weeks of injury, assessed at 3 months post-TBI, and produced nonacquiescent profiles. Assessments collected included the SITS (comprising open-ended and closed-ended questions), Rivermead Post Concussion Symptoms Questionnaire (RPQ), Sport Concussion Assessment Tool-3 (SCAT-3) symptom checklist, and Minnesota Multiphasic Personality Inventory-2 Restructured Form True Response Inconsistency (TRIN-r) scale. Results: Current mTBI symptom burden and individual symptom endorsement were highly concordant between SITS closed-ended questions, the RPQ, and the SCAT-3. Within the SITS, participants reported significantly fewer mTBI symptoms to open-ended as compared to later closed-ended questions, and this difference was weakly correlated with TRIN-r. Symptom scales were weakly associated with TRIN-r. Conclusions: mTBI symptom reporting varies primarily by whether questioning is open- vs. closed-ended but not by mode of assessment (interview, questionnaire). Acquiescence response bias appears to play a measurable but small role in mTBI symptom reporting overall and the degree to which participants report more symptoms to closed- than open-ended questioning. These findings have important implications for mTBI research and support the validity of widely used TBI symptom inventories.